The Effect of the Flipped Classroom Learning Model on Students’ Learning Outcome in Multivariable Calculus Course - Triana Harmini; Nugroho Arif Sudibyo; Siti Suprihatiningsih (AlphaMath : Journal of Mathematics Education, 2022)
The COVID-19 pandemic that occurred starting in early December 2019 had a major impact on the world of education. Therefore, it is necessary to develop a flipped classroom-based mathematical learning model. The purpose of this study was to find out the effect of flipped classroom-based mathematical learning model on students of the Mathematics Education study program on Multivariable Calculus courses. This research is a pseudo-experimental study. The subject of this study is a mathematics education student who is pursuing multivariable calculus courses that are directly involved in the learning model applied at West Kalimantan which is divided into two classes with each class consisting of 15 students. Experimental classes are given learning using Flipped Classroom-based learning models while control classes are given learning with online learning using google classroom. This research design uses a randomized control group posttest only design. Data analysis techniques also use Mann-Whitney nonparametric hypothesis tests. The results of the study that has been conducted show a significance value of 0.015 less than the significance level of 0.05 so it can be concluded that there is a real difference between the control learning model and the Flipped Classroom model or the flipped classroom learning model effective to improve student learning outcomes.